1971
DOI: 10.1139/o71-030
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Factor for Photophosphorylation in Bean Etioplasts and Chloroplasts

Abstract: Extracts from either bean chloroplasts or etioplasts stimulate photophosphorylation in partially deficient chloroplast residues. Both extracts contain a latent Ca2+-dependent ATPase but the specific activity of the chloroplast extract is about sevenfold higher. The etioplast ATPase appears to have identical properties to a spinach chloroplast ATPase that has been shown to be a modified coupling factor for photophosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

1972
1972
1979
1979

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Bean (Phaseolus vulgaris L.) etioplasts and chloroplasts were prepared, and the coupling factor was extracted with EDTA as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bean (Phaseolus vulgaris L.) etioplasts and chloroplasts were prepared, and the coupling factor was extracted with EDTA as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…ATPase activity of the DTT-activated EDTA extracts was measured according to McCarty and Racker (24) under conditions described in the previous paper (12). RuDP carboxylase of the extracts was assayed according to Bradbeer (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated that the unit of membrane assembly in maize thylakoids is different from the unit of photosynthetic function of these membranes. The coupling factor for phosphorylation also occurs in bean etioplasts (6).…”
mentioning
confidence: 97%
“…This demonstrated that the unit of membrane assembly in maize thylakoids is different from the unit of photosynthetic function of these membranes. The coupling factor for phosphorylation also occurs in bean etioplasts (6).A/B phos3 is the production by chloroplast thylakoids of ATP upon transfer of membrane vesicles from an acidic to an alkaline solution in the presence of ADP and inorganic phosphate (7). This reaction occurs in darkness and is entirely independent of the capture of quanta by Chl.…”
mentioning
confidence: 99%